2006
DOI: 10.1093/ndt/gfl387
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of intravenous darbepoetin alfa administered once every 2 weeks in chronic kidney disease patients on haemodialysis

Abstract: The treatment of renal anaemia in HD patients with i.v. Q2W darbepoetin alfa effectively and safely maintains Hb concentrations at a less frequent dosing regimen than observed with QW administration. Dose requirements for i.v. darbepoetin alfa administered QW or Q2W were not different. The results of this study demonstrate that i.v. darbepoetin alfa administered Q2W is an effective regimen for HD patients requiring anaemia treatment in routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Increased specific activity of darbepoetin alfa compared with rHuEPO was also reported in human clinical studies [56]. In humans administered darbepoetin alfa with a Q2W (every other week) dosing regimen, the same total dosage could successfully maintain Hb levels in renal anemic dialysis patients in comparison with QW (weekly) administration of the drug [57]. Similarly, in the predialysis population, QM (monthly) administration of the drug maintained Hb concentration at the same total dose in comparison with Q2W administration [58].…”
Section: Successful Development Of Darbepoetin Alfamentioning
confidence: 73%
“…Increased specific activity of darbepoetin alfa compared with rHuEPO was also reported in human clinical studies [56]. In humans administered darbepoetin alfa with a Q2W (every other week) dosing regimen, the same total dosage could successfully maintain Hb levels in renal anemic dialysis patients in comparison with QW (weekly) administration of the drug [57]. Similarly, in the predialysis population, QM (monthly) administration of the drug maintained Hb concentration at the same total dose in comparison with Q2W administration [58].…”
Section: Successful Development Of Darbepoetin Alfamentioning
confidence: 73%
“…administration of ESAs to dialysis patients (15). Several earlier studies demonstrated that darbepoetin-alpha can be given once every 2 weeks (Q2W) and maintains hemoglobin levels in hemodialysis patients , in 2006 the results of the study done by Carrera et al (20), fully support the practical use of the i.v. Q2W darbepoetin-alpha regimen in stable HD patients switched from once weekly dosing.…”
Section: Discussionmentioning
confidence: 89%
“…Thirty (83%) of those evaluable patients successfully maintained the target haemoglobin with no or minimal dose increased required to maintain the required hemoglobin concentration , while their conversion regimen was unsuccessful in 6 patients and was concluded that darbepoetin-alpha administered once monthly, maintained hemoglobin effectively and safely in most dialysis patients stabilized previously on once every 2 weeks dosing however the median weekly dose of darbepoetin-alpha increased from (15 units , CI =11. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] at the start of the study to (21.88 units, CI =12. 31-31.25) .…”
Section: Discussionmentioning
confidence: 99%
“…15 Several earlier studies demonstrated that darbepoetin alfa can be given once every 2 weeks and maintains Hgb levels in hemodialysis patients. In 2006, the results of the study done by Carrera et al, 20 fully supported the practical use of the once every-2-week IV darbepoetin alfa regimen in stable HD patients switched from once-weekly dosing.…”
Section: Discussionmentioning
confidence: 91%